Bioactivities of Murraya koenigii (Linn.) and Adina cordifolia (Roxb.) - Tahia, Faiza; Sikder, Md Al Amin; Sayeed, Mohammad A; Rashid, Mohammad A (Bangladesh Pharmaceutical Journal, 2015)
The present study was designed to evaluate the antioxidant, cytotoxic, thrombolytic, membrane stabilizing and antimicrobial activities of methanol extracts and different organic soluble partitionates of leaves of Murraya koenigii and bark of Adina cordifolia. In the DPPH free radical scavenging assay, the chloroform soluble fraction of methanol extracts of M. koenigii and A. cordifolia revealed the highest free radical scavenging activity with IC50 values of 6.9 ± 0.78 ?g/ml and 6.83 ± 0.29 ?g/ml, while the methanolic crude extract of M. koenigii and A. cordifolia displayed the highest cytotoxic potential having LC50 values of 1.94 ± 0.36 ?g/ml and 0.88 ± 0.64 ?g/ml, respectively as compared to standard vincristine sulphate (LC50 value of 0.45 ?g/ml). During assay for thrombolytic activity, the crude extracts of M. koenigii and A. cordifolia showed 8.6 ± 0.48 % and 9.25 ± 0.84% clot lysis, respectively. In the membrane stabilizing assay, the methanol extract of M. koenigii inhibited 62.80 ± 0.81 % and 21.23 ± 0.84 % hypotonic solution- and heat-induced haemolysis of RBCs as compared to 72.2 % and 42.2 % inhibition by acetyl salicylic acid (0.10 mg/ml), respectively. On the other hand, the methanol extract of A. cordifolia demonstrated 42.04 ± 0.57 % and 21.57 ± 0.22 % inhibition of hypotonic solution- and heat-induced hemolysis, respectively. The extractives of A. cordifolia exhibited antibacterial activity with zone of inhibition ranging from 8.0 to 26.0 mm against the test microorganisms with the highest zone of inhibition (26.0 mm) against Salmonella Typhi. Although the methanol extract of leaf of M. koenigii as well as its pet ether and aqueous soluble fractions demonstrated no antimicrobial activity, the carbon tetrachloride soluble fraction (CTC) revealed moderate antibacterial activity against Staphylococcus aureus (16.0 mm). Bangladesh Pharmaceutical Journal 18(1): 25-29, 2015